Improving the Quality of Learning Through the Integration of Literacy and Numeracy - Tiur Malasari Siregar; Muliawan Firdaus; Trisnawati Hutagalung; Irham Ramadhani; Suci Frisnoiry (Jurnal Penelitian Pendidikan IPA, 2025)
Quality learning requires the systematic integration of literacy and numeracy as foundational competencies that support students’ critical thinking, problem-solving abilities, and overall academic achievement. This literature review aims to identify the specific strategies used to integrate literacy and numeracy and evaluate their impact on critical thinking, conceptual understanding, and student engagement within the Indonesian education context. A narrative literature analysis was conducted by reviewing empirical studies, national education reports, and policy documents published between 2009-2023. Sources were screened based on their relevance to integration models, curriculum implementation, and measurable learning outcomes. The findings indicate that literacy–numeracy integration is most effective when implemented through contextual learning materials, project-based learning, and the Independent Curriculum, which collectively enhance students’ analytical thinking and comprehension of academic concepts. Evidence also shows that literacy-focused interventions and expanded access to learning resources increase motivation and engagement, although numeracy performance remains comparatively lower and requires stronger reinforcement. Overall, this review demonstrates that meaningful integration of literacy and numeracy contributes significantly to students’ readiness to engage with complex academic tasks. The study concludes that targeted integration strategies, supported by appropriate curriculum structures and equitable access to learning resources, are essential for improving learning quality across educational levels.